2019
DOI: 10.33750/ijhi.v2i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Using portfolio assessment to improve EFL students’ expository-writing performance

Abstract: The objectives of the research were to find out the extent to which the use of portfolio assessment improves EFL students' performances in expository-writing and to find out the students' responses about the taking of portfolio assessment in improving their performance in writing expository text. The researcher applied classroom action research which was done through two cycles. The location of this research was at one of the secondary schools in Makassar, South Sulawesi, Indonesia. There were 31 students as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…They concluded that students in general consider portfolio as a fair assessment tool that has the potential to motivate students. EFL learners with a portfolio assessment would result in a satisfactory performance on EFL expository-writing (Dahviyanti & Iskandar, 2019). We can refer to the findings of previous studies (Wang & Liao, 2008;Tabatabaei & Assefi, 2012;Roohani & Taheri, 2015) which stated, using portfolios did have significant impact on ELF students' writing performance.…”
Section: Literature Reviewmentioning
confidence: 76%
“…They concluded that students in general consider portfolio as a fair assessment tool that has the potential to motivate students. EFL learners with a portfolio assessment would result in a satisfactory performance on EFL expository-writing (Dahviyanti & Iskandar, 2019). We can refer to the findings of previous studies (Wang & Liao, 2008;Tabatabaei & Assefi, 2012;Roohani & Taheri, 2015) which stated, using portfolios did have significant impact on ELF students' writing performance.…”
Section: Literature Reviewmentioning
confidence: 76%
“…A study into the history of language teaching and pedagogy suggests that there has been a close interrelationship between language teaching and assessment. Writing skill is the most neglected area in language learning [1,2]. It seems to have more agreement that speaking and listening are the skills most needed when trying to succeed in a foreign language environment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Portfolio procedure, a major aspect in PBTHT, to teach writing indicated successful results (Shokraie & Tabrizi, 2016). Portfolio assessment affected the enhancement of content, organization, vocabulary, grammar, and mechanics (Syafei, et al, 2020;Efendi et al, 2017;Prastikawati et al, 2016;Dahviyanti & Iskandar, 2019).…”
Section: Portfolio-based Timed-handwriting Technique (Pbtht)mentioning
confidence: 99%